Principles And Methods Of psychological Correction Of Women Personality’s Gender Functioning - Kocharian, Oleksandr; Pospelova, Svetlana; Frolova, Evgeniya (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2016)
The work considers the issues of some problems of gender functioning psychological correction of modern young women, that were identifid in the study: prevalence of immature sex-role types; masculinity/femininity symptom-complex ego-dystonity; femininity defiiency; gender-role behavior differentiation lack, rigidity and misery. The article proposes a psychological correction program that focuses on improving sexrole and personality maturity. The group form of work is realized in program, built on the person-centered therapy basis. In technical terms, the program is multi-modal. The results of program effectiveness evaluated by using the comparative analysis of preliminary tests and post-test results. The changes that occurred after the end of women participation in psychological correction are analyzed.